2007
DOI: 10.4049/jimmunol.179.10.6881
|View full text |Cite
|
Sign up to set email alerts
|

Targeting IFN-α to B Cell Lymphoma by a Tumor-Specific Antibody Elicits Potent Antitumor Activities

Abstract: IFN-α, a cytokine crucial for the innate immune response, also demonstrates antitumor activity. However, use of IFN-α as an anticancer drug is hampered by its short half-life and toxicity. One approach to improving IFN-α’s therapeutic index is to increase its half-life and tumor localization by fusing it to a tumor-specific Ab. In the present study, we constructed a fusion protein consisting of anti-HER2/neu-IgG3 and IFN-α (anti-HER2/neu-IgG3-IFN-α) and investigated its effect on a murine B cell lymphoma, 38C1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
41
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 47 publications
(43 citation statements)
references
References 42 publications
1
41
0
Order By: Relevance
“…The literature suggests that targeted IFN␣ might also induce an acute tumor-directed immune response and evoke immune memory. 21,22 Because murine cells are considerably less sensitive (ϳ 4 logs) than human cells to human IFN␣2b, 23,24 the antitumor activity of mAb-IFN␣ in murine models is primarily because of the direct action of IFN␣2b on the tumor cells and cannot be attributed to immunoactivation in the host. In the ex vivo studies, C2-2b-2b depleted normal B cells, monocytes, and DCs.…”
Section: Discussionmentioning
confidence: 99%
“…The literature suggests that targeted IFN␣ might also induce an acute tumor-directed immune response and evoke immune memory. 21,22 Because murine cells are considerably less sensitive (ϳ 4 logs) than human cells to human IFN␣2b, 23,24 the antitumor activity of mAb-IFN␣ in murine models is primarily because of the direct action of IFN␣2b on the tumor cells and cannot be attributed to immunoactivation in the host. In the ex vivo studies, C2-2b-2b depleted normal B cells, monocytes, and DCs.…”
Section: Discussionmentioning
confidence: 99%
“…Our strategy of fusing IFN to antibody has several major advantages in vivo. While the half-life of IFNa is only 1 h, 26 we have shown that fusing it to IgG extends the half-life to 8 h. 10,11 In addition, the anti-CD138 portion of the fusion protein provides a binding specificity to target MM and deliver therapeutically useful levels of IFN without systemic toxicity. Indeed, we have shown the effectiveness of this strategy in targeting not only MM, 8 but also lymphoma using anti-CD20-IFNa2.…”
Section: Combination Of Anti-cd138-ifna14 and Bortezomib Provides Enhmentioning
confidence: 84%
“…27,28 Previous studies in our laboratory [8][9][10][11] have shown that genetic fusion of IFNs to an antibody is an effective strategy to specifically target IFN to the tumor microenvironment, reduce systemic toxicity, and increase half-life.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations